Literature Review of Korosanai Maaththirai in Suvaasa Noi - Nithyapriya, S.; Sivashanmugarajah, S. (Global Academic Research Institute Colombo, Sri Lanka, 2021)
Kapa dosha usually increase in respiratory diseases. Pungent vipaka will reduce Kapa dosha. Korosanal is one of the pungent drugs. It is better management for Suvaasa nol and its symptoms in Children. The objective of the study "to study the organoleptic chacerctors. Korosanai in Suvaasa noi”, Irumal noi, iraippu noi, Peenisam and ilaiipu are some Suvaasa nol. In allopathic system Suvaasaasya rogam called as Respiratory diseases. Irumal Noi is a disease in Siddha, but it is one of the symptoms in allopathic system, which correlated with cough. Iraippu nol is correlated with Bronchial asthma. Peenisam is correlated with sinusitis. Ilaippu noi is correlated with tuberculosis. These are common in children society. More than eighty in hundred children affected by Respiratory diseases. Repeated respiratory sign and symptoms cause serious health problems. So we have take prevent the respiratory system complaints in earlier. It is a literature study. All relevant information for this study was gathered from Manuscripts at V.Chellalyah Siddha Ayurvedic medical center. So far no researcher has been undertaken this study and this Korosanal method was specially came from Traditional doctor's ancestors, Therefore the researcher has selected the study of the about this study. Dyspnoea, rhinorrhoea, cough, sneezing often accompanied by nasal obstruction. In Korosanal,68.42% (13) of the raw material have Pungent taste, 15.79% (3) has bitter taste, Ihas sour, Ihas sweet, 1 has astringent.89.47% (17) has ushna property and 10.53% (2) has seetha property. 94.73% (18) of the raw material has pungent vipaka and one has sweet vipaka. This study concluded in Korosanal Majority 94.73% of raw materials has pungent vipaka. Therefore Korosanal Maaththirai is very effective for Kapa diseases.
Keywords: Korosanal maaththirai; Suvaasa noi; Pungent vipaka